Rhythmic patterns of discharge in hypothalamic neurosecretory neurons of cats and dogs. - Yamashita, H (1979)
Recent studies in rats suggest that vasopressin- and oxytocin-secreting neurons in supraoptic nuclei and paraventricular nuclei of the hypothalamus show two different patterns of activity: one a "bursting" or rhythmic pattern and the other, irregular continuous discharges. This possibility was investigated in cats and dogs anesthetized with chloralose or Nembutal by recording electrical activity of single supraoptic and paraventricular neurons. Only some of the "identified" neurosecretory cells showed rhythmic, intermittent discharges ("bursting" cells in rats); the majority showed an irregular continuous firing pattern. Furthermore, the pattern of discharge sometimes changed from one ot the other during long periods of observation. This occurred without apparent stimulus in certain instances; in others, the rhythmic firing was associated with fluctuation in blood pressure and heart rate and was likely to be caused by changes in baroreceptor activity. Possible origins of rhythmic discharges and the physiological importance of such patterns in terms of hormone secretion are discussed.